Analisis Pendapatan Asli Daerah Kabupaten/Kota di Provinsi Daerah Istimewa Yogyakarta - Laila, Hafidah; Triwahyuningtyas, Nunuk; Aminda, Renea Shinta (Jurnal Indonesia Sosial Sains, 2022)
This research aims to determine the effect of population, per capita income, and government spending on Regional Original Income (PAD) in regencies/cities in the Special Region of Yogyakarta (DIY). The sampling in this study used the saturated sampling method in 5 regions during 2013-2019, so a total sample of 35 data was obtained from the Central Statistics Agency (BPS). This research uses a data analysis panel that is a mixture of cross section data and time series data. The results of the research partially show that population and per capita income have a significant positive effect on PAD, while government spending does not affect PAD. The research results simultaneously show that population, per capita income, and expenditure affect PAD.